2021
DOI: 10.1123/japa.2019-0395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enriched Physical Activity Environments on Balance and Fall Prevention in Older Adults: A Scoping Review

Abstract: The incidence of falling, due to aging, is related to both personal and environmental factors. There is a clear need to understand the nature of the major risk factors and design features of a safe and navigable living environment for potential fallers. The aim of this scoping review was to identify studies that have examined the effectiveness of environments, which promote physical activity and have an impact on falls prevention. Selected studies were identified and categorized into four main topics: built en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…However, our findings showed that even in moderate frail older adults or older adults with falls, the home-based fall prevention programmes were effective in reducing the fall rate [19,38] and improved physical function [35,36,38]. The results of other review studies also showed that community-based multifunctional interventions reduced the fall rate by 32% [48] and improved balance [47] in older adults with dementia.…”
Section: Individually Tailored Programme and Amount Of Supervisionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, our findings showed that even in moderate frail older adults or older adults with falls, the home-based fall prevention programmes were effective in reducing the fall rate [19,38] and improved physical function [35,36,38]. The results of other review studies also showed that community-based multifunctional interventions reduced the fall rate by 32% [48] and improved balance [47] in older adults with dementia.…”
Section: Individually Tailored Programme and Amount Of Supervisionmentioning
confidence: 49%
“…To maximise the benefits of home-based interventions, it is necessary to adopt a balanced approach through occasional visits by health carers to monitor progress, online and face-to-face feedback provision to build up self-efficacy and correction of errors and remote support throughout the intervention period to enhance adherence [43,46]. Another limitation of home-based interventions is the level of frailty and cognitive function of participants; the level of frailty and muscle weakness might limit the feasibility of home-based interventions as more supervision is required [47]. However, our findings showed that even in moderate frail older adults or older adults with falls, the home-based fall prevention programmes were effective in reducing the fall rate [19,38] and improved physical function [35,36,38].…”
Section: Individually Tailored Programme and Amount Of Supervisionmentioning
confidence: 99%
“…The experience of falls can also cause fear of falling, social isolation, and decreased physical activity, resulting in a decline in overall health and well-being [14][15][16]. Monitoring dynamic balance during activities is critical for fall prevention in the elderly [17,18].…”
Section: Introductionmentioning
confidence: 99%